Behavior of cellular beams protected with intumescent coatings - Lamri, Brahim (2018)
A new engineering practice in modern buildings is to use beams with web openings to allow the passage of services within the depth of the beam instead of underneath the beam. As the web post failure may occur before the section reaches the limiting temperature, usually an increase in the fire protection may be required for members with web openings in comparison to its equivalent solid section. The aim of this work is to present an experimental study of unloaded solid and cellular beams with circular holes in fire conditions with and without intumescent fire protection. These preliminary tests results are the basis for generating an elemental multi-temperature analysis needed to assess cellular beams with intumescent protection and give experimental results for calibration of further numerical simulations. The experimental results show that, considering the same nominal fire protection thickness, one can obtain a higher fire resistance time for solid beams when compared with cellular beams. The tests performed, with different hole diameters and web-post widths, points that to achieve the same fire resistance time, a cellular beam will need a higher fire protection compared to an equivalent solid beam. Also, a special care is needed when the intumescent coating is applied around the hole to avoid the intumescent contraction, applying for example an over coating.